Kualitas Isi dan Kalimat Efektif pada Teks Berita di Website Detikjabar Edisi Februari 2024 sebagai Bahan Bacaan dan Sumber Informasi bagi Mahasiswa - Adhwa Farah Yosinta; Anton April Laksono; Intana Aura Izza; Wahidah Mustaqimah; Wanda Sukmawati; Asep Purwo Yudi Utomo; Galih Suci Pratama (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Ineffective sentences are sentences that have several words that are difficult to understand. This research is motivated by the writers in the preparation of sentences in news texts that are not in accordance with linguistic rules. This research aims to identify the use of effective sentences in online news texts, with a focus on the article